2018
DOI: 10.1177/2055207618780499
|View full text |Cite
|
Sign up to set email alerts
|

The impact of YouTube peer feedback on attitudes toward recovery from non-suicidal self-injury: An experimental pilot study

Abstract: Background Non-suicidal self-injury (NSSI) is a serious public health concern facing adolescents and young adults worldwide. Despite growing concern that accessing NSSI content on the internet may negatively influence perceptions toward NSSI recovery, no studies have examined actual impacts. Objectives This experimental pilot study assessed the impact of exposure to hopeless versus hopeful peer messages on perceptions toward NSSI recovery. It was hypothesized that expos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 19 publications
1
18
0
2
Order By: Relevance
“…Over-reporting of negative comments in the current study might be an indication of those comments having a very high emotional impact on affected adolescents and might pose a risk-factor for worsening of mood, increased feelings of rejection and therefore possibly increasing or persisting NSSI. On another note, in a recent experimental study, participants who were exposed to hopeful comments under NSSI content on YouTube showed a significant increase in their attitudes towards recovery, while negative comments did not show a negative effect (27). As adolescents keep posting pictures on social media despite the risk of being verbally harassed, the effect of positive feedback and social support (with possible positive effects on recovery) should be further explored.…”
Section: Discussionmentioning
confidence: 98%
“…Over-reporting of negative comments in the current study might be an indication of those comments having a very high emotional impact on affected adolescents and might pose a risk-factor for worsening of mood, increased feelings of rejection and therefore possibly increasing or persisting NSSI. On another note, in a recent experimental study, participants who were exposed to hopeful comments under NSSI content on YouTube showed a significant increase in their attitudes towards recovery, while negative comments did not show a negative effect (27). As adolescents keep posting pictures on social media despite the risk of being verbally harassed, the effect of positive feedback and social support (with possible positive effects on recovery) should be further explored.…”
Section: Discussionmentioning
confidence: 98%
“…Within the network of participants posting pictures of NSSI, universal preventative measures could be implemented, as a large number of those young people seem to be at risk for suicide. Furthermore, there seems to be a potential for using social media in a protective way, as it has recently been shown that fictional peer comments, can have an impact to positively change attitudes towards recovery from NSSI [42].…”
Section: Discussionmentioning
confidence: 99%
“…For example, research examining online NSSI content indicates that NSSI is often portrayed using hopeless tones that emphasise emotional pain without mention of encouragement of recovery; in other cases, NSSI is presented as an acceptable means of coping with emotional pain. 1,5 Hence, mention of alternative means of coping is rare. Such portrayals, especially if repeatedly accessed, may lead to continued NSSI and thwarted help-seeking efforts.…”
Section: Rationale For Media Guidelinesmentioning
confidence: 99%